Carbon Emission Disclosure, Corporate Social Responsibility, Green Accounting : Firm Value Moderated by Profitability - Alya Diajeng Pangestu; Nawirah Nawirah (Owner : Riset dan Jurnal Akuntansi, 2025)
Firm value, as used in accounting, is the value derived from the market and represented by stock prices. Among the elements that influence firm value are carbon disclosure, CSR, and green accounting. By applying profitability as a control variable, this study examines how carbon disclosure, CSR, and green accounting impact firm value. A total of 186 energy and basic materials companies listed on the Indonesia Stock Exchange were the subjects of the study. The sample for this study includes 14 companies from the energy & basic materials sector that regularly publish sustainability reports and annual reports with regard to profitability between 2021 and 2023. The sample for this study consists of 14 companies from the energy and basic materials sector that regularly release sustainability reports and annual reports for the years 2021-2023 with regard to profitability. In this study, Eviews 12 software was used to conduct panel data regression analysis and modified regression analysis (MRA). The findings show that although carbon disclosure and green accounting have no impact on firm value, corporate social responsibility (CSR) significantly affects it. Furthermore, corporate profitability does not increase or decrease the impact of CSR, carbon disclosure, and green accounting on firm value.